Le plan local d’urbanisme français : un instrument orienté de pédagogie citoyenne du paysage - Mathieu Gigot; Arnaud de Lajartre (Projets de Paysage)
Local urban development plans (in French, Plan local d’urbanisme, PLU) in their various components focus greatly on the landscape thus contributing in the field to a form of pedagogy of the landscape for citizens; this takes place at two levels which will be addressed in the two parts of the article. Social situations which teach about the landscape occur in the elaboration of the PLU and in its implementation with the submissions for building permits involving exchanges between the local authorities and the inhabitants and subsequently between petitioners and the building permit office. Whatever meaning is given to the term “landscape”, these discussions provide didactic opportunities. However, we will demonstrate that in substance this pedagogy of the landscape is often founded on a semantic shift between landscape and heritage, which varies according to the opposability of the components of the PLU. From the landscape as a living environment in a sustainable urban development plan there is often a shift towards a regulatory framework defining the landscape purely in heritage terms. For the inhabitants this fosters an oriented representation of the landscape at the service of which several mediation documents apply.